(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
The transgender community has faced and continues to face discrimination in almost every part of the world. The inception, extent, and duration of such differential treatment coupled with violence may differ across the globe. The reason behind this could be the cultural and constitutional values of the concerned nation along with the traditional position of transgenders in the relevant society. The movement of LGBT community to assert their presence and voice their concerns can be traced in different countries. Argentina can be distinguished as a vanguard in the advancement of inclusive policies, notably with the passage of its Gender Identity Law in 2012, marking it as the inaugural nation worldwide to formally acknowledge an individual’s gender identity without imposing any prerequisites. This article provides a concise overview of the historical trajectory of the LGBT movement in Argentina, followed by an examination of the constitutional and legislative framework established to safeguard the rights of transgender individuals in the country. Subsequently, it delves into the enactment and notable attributes of the Gender Identity Law. It also provides a comparative analysis of transgender law in India vis a vis Argentina and criticises the contrasting approach followed by different States of India. It concludes with the finding that Argentina’s Gender Identity Law is quite progressive from which countries like India can take inspiration.